Benchmark study for multiple security documents enhancing SPIFFE/SPIRE environment - Cochak, Henrique Zanela; Miers, Charles Christian (Anais da Escola Regional de Alto Desempenho da Região Sul (ERAD-RS), 2024)
After specifying and creating new security tokens and cryptographic algorithms under the ‘Secure Federated Identity Management: Enhancing and Extending the SPIFFE Architecture” project, a performance assessment is required to measure and compare the computational efficiency, execution speed, and resource consumption of each security token and algorithm. This paper proposes the analysis employing Docker and Kubernetes environments as initial study cases.